Neil Flambé and the Aztec abduction - Sylvester, Kevin (Sylvester, Kevin. Neil Flambé capers, 2010)
Teen chef Neil Flambé heads to Mexico City to participate in the Azteca Cocina cooking competition, hoping to win money to pay off a huge loan he took out to make renovations to his restaurant, but everything starts to go wrong when kidnappers snatch his girlfriend Isabella and threaten to kill her if Neil does not throw the contest.